Learning to govern together in representative democracy the dynamics of cooperation and competition in coalition governance - König, Thomas 1961-; Lu, Xiao 1992-; Silva, Thiago N. (Oxford University Press, 2025)
Learning to Govern Together in Representative Democracy introduces a dynamic theory of coalition governance, focusing on the temporal constraints that coalition parties face when governing together in representative democracies. The book examines how coalition partners, over the course of a legislative term, adapt their strategies for joint policy-making as they encounter varying levels of cooperation and competition in partnership. Two distinct models of learning are developed: the portfolio-learning model, where ministers learn through interactions within their portfolios, and the partisan-learning model, which accounts for learning from co-partisan experiences across portfolios. Empirical evidence from 11 parliamentary democracies demonstrates that ministerial office-holders infer the type of partnership from their experienced parliamentary scrutiny, with consequences for their legislative behavior, such as initiating government bill proposals earlier in the term if they perceive a cooperative partnership, or later in the term if they perceive a competitive partnership. The book makes a significant contribution to our understanding of coalition effectiveness, stability, and satisfaction with governance.
Literaturverzeichnis Seite [137]-142
Keywords: Repräsentative Demokratie; Koalition; Coalition governments; Representative government and representation; Democracy; Comparative government; Gouvernement représentatif